Food Microbiology Protocols - Spencer, John F. T.; Ragout de Spencer, Alicia L.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2001)
Microorganisms participate in both the manufacture and spoilage of foodstuffs. In Food Microbiology Protocols, expert laboratorians present a wide ranging set of detailed techniques for investigating the nature, products, and extent of these important microorganisms. The methods cover pathogenic organisms that cause spoilage, microorganisms in fermented foods, and microorganisms producing metabolites that affect the flavor or nutritive value of foods. Included in the section dealing with fermented foods are procedures for the maintenance of lactic acid bacteria, the isolation of plasmid and genomic DNA from species Lactobacillus, and the determination of proteolytic activity of lactic acid bacteria. A substantial number of chapters are devoted to yeasts, their use in food and beverage production, and techniques for improving industrially important strains. There are also techniques for the conventional and molecular identification of spoilage organisms and pathogens, particularly bacteria, yeasts, and the molds that cause the degradation of poultry products. Each method is described step-by-step for assured results, and includes tips on avoiding pitfalls or developing extensions for new systems.. Comprehensive and timely, Food Microbiology Protocols is a gold-standard collection of readily reproducible techniques essential for the study of the wide variety of microorganisms involved in food production, quality, storage, and preservation today.
Spoilage Organisms -- Psychrotrophic Microorganisms -- Biochemical Identification of Most Frequently Encountered Bacteria That Cause Food Spoilage -- Mesophilic Aerobic Microorganisms -- Yeasts and Molds -- Coliforms -- Genetic Analysis of Food Spoilage Yeasts -- Pathogens -- Conductimetric Method for Evaluating Inhibition of Listeria monocytogenes -- Molecular Detection of Enterohemorrhagic Escherichia coli O157:H7 and Its Toxins in Beef -- Detection of Listeria monocytogenes by the Nucleic Acid Sequence-Based Amplification Technique -- Detection of Escherichia coli O157:H7 by Immunomagnetic Separation and Multiplex Polymerase Chain Reaction -- Detection of Campylobacter jejuni and Thermophilic Campylobacter spp. from Foods by Polymerase Chain Reaction -- Magnetic Capture Hybridization Polymerase Chain Reaction -- Enterococci -- Salmonella -- Campylobacter -- Listeria monocytogenes -- Fermented Foods -- Methods for Plasmid and Genomic DNA Isolation from Lactobacilli -- Methods for the Detection and Concentration of Bacteriocins Produced by Lactic Acid Bacteria -- Meat Protein Degradation by Tissue and Lactic Acid Bacteria Enzymes -- Maintenance of Lactic Acid Bacteria -- Probiotic Properties of Lactobacilli -- Identification of Exopolysaccharide-Producing Lactic Acid Bacteria -- Differentiation of Lactobacilli Strains by Electrophoretic Protein Profiles -- Methods to Determine Proteolytic Activity of Lactic Acid Bacteria -- Methods for Isolation and Titration of Bacteriophages from Lactobacillus -- Identification of Yeasts Present in Sour Fermented Foods and Fodders -- Organisms in the Manufacture of Other Foods and Beverages -- Protein Hydrolysis -- Production of Polyols by Osmotolerant Yeasts -- Identification of Yeasts from the Grape/Must/Wine System -- Carotenogenic Microorganisms -- Genetic and Chromosomal Stability of Wine Yeasts -- Prediction of Prefermentation Nutritional Status of Grape Juice -- Enological Characteristics of Yeasts -- Utilization of Native Cassava Starch by Yeasts -- Methods and Equipment -- Reactor Configuration for Continuous Fermentation in Immobilized Systems -- Molecular Characterization of Yeast Strains by Mitochondrial DNA Restriction Analysis -- Selection of Yeasts Hybrids Obtained by Protoplast Fusion and Mating, by Differential Staining, and by Flow Cytometry -- Selection of Hybrids by Differential Staining and Micromanipulation -- Flotation Assay in Small Volumes of Yeast Cultures -- Obtaining Strains of Saccharomyces Tolerant to High Temperatures and Ethanol -- Multilocus Enzyme Electrophoresis -- Bacteriocin Production Process by a Mixed Culture System -- Reviews -- Nutritional Status of Grape Juice -- Problems with the Polymerase Chain Reaction -- Problems with Genetically Modified Foods.
Keywords: Microbiology; Microbiology